Supporting Independence in Adolescents on the Autism Spectrum. (March 2014) - Hume, Kara; Boyd, Brian A.; Hamm, Jill V.; Kucharczyk, Suzanne
The development of independent behavior is a critical, challenging process for all youth as they pass through the high school environment into adulthood. Although most high school students gain skills related to independence, the independent behaviors of their peers with autism spectrum disorder (ASD) plateau and decline. These skill deficits and resulting poor post-secondary outcomes for students with ASD highlight the great need for programming in this area. This article begins by defining independence and the influence of independence on post-secondary outcomes, and explores the factors that contribute to the difficulties in independence for individuals with ASD. Then, a review of school-wide positive behavior support and focused evidence-based practices (EBPs) related to independence is presented. Recommendations are made for practitioners and caregivers implementing interventions intended to support student independence, and recommendations for future research and practice are offered.